Is the Therapeutic Alliance Associated with and Predictive of Treatment Retention and Outcome Among Latinos?: A Secondary Analysis of an RCT of Behavioral Activation for Latinos with Depression Versus Treatment-as-Usual - (:unkn) unknown (My University, 2016)
A robust association between the therapeutic alliance and various forms of psychotherapy outcome has been demonstrated. The therapist-client alliance has been shown to be associated with and predictive of dropout and depression symptom change with primarily U.S. White samples. The current study examines whether the alliance is associated with retention, as measured by dropout and session attendance, and depression change in a sample of low-income Spanish-speaking Latinos in the U.S. who received Behavioral Activation for Latinos (BAL) with depression or treatment-as-usual (TAU). Given the proposition that BA treatment fosters the alliance systematically throughout treatment, and that usual treatment was not guided by a protocol that required systematic implementation of alliance-fostering techniques, BAL was expected to evidence higher alliance scores compared to TAU. Alliance was also examined as a predictor of these outcome variables. For BAL, alliance scores were expected to predict lower likelihood of dropout, higher session attendance, and higher depression change after controlling for early gains when compared to TAU. Findings in support of the alliance as a predictor of retention and outcome would point to potential areas of intervention for improving psychotherapy treatment retention and depression outcome in Latino communities. Current findings did not show that the alliance was associated with or predicted retention or depression change for this sample. Methodological limitations of this study are discussed.
Keywords: Behavioral Activation; Depression Change; Latinos; Retention; Therapeutic Alliance